2019
DOI: 10.1002/mabi.201900161
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Micelles Loading Proteins through Concurrent Ion Complexation and pH‐Cleavable Covalent Bonding for In Vivo Delivery

Abstract: Protein drugs have great potential as targeted therapies, yet their application suffers from several drawbacks, such as instability, short half‐life, and adverse immune responses. Thus, protein delivery approaches based on stimuli‐responsive nanocarriers can provide effective strategies for selectively enhancing the availability and activation of proteins in targeted tissues. Herein, polymeric micelles with the ability of encapsulating proteins are developed via concurrent ion complexation and pH‐cleavable cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 43 publications
0
27
0
2
Order By: Relevance
“…However, the toxicity of these linkers lowers the biocompatibility and the irreversible crosslinking hampers the triggered release of the protein at the targeted site. This has motivated the development of reversible crosslinking strategies involving labile bonds, which can be cleaved upon specific environmental triggers, allowing the C3Ms to be stable at physiological conditions but disassemble at the site of action [ 113 , 114 , 115 , 116 ]. For example, crosslinking via disulphide bonds yielded highly stable C3Ms under physiological conditions.…”
Section: Biotechnological Applications Of C3msmentioning
confidence: 99%
“…However, the toxicity of these linkers lowers the biocompatibility and the irreversible crosslinking hampers the triggered release of the protein at the targeted site. This has motivated the development of reversible crosslinking strategies involving labile bonds, which can be cleaved upon specific environmental triggers, allowing the C3Ms to be stable at physiological conditions but disassemble at the site of action [ 113 , 114 , 115 , 116 ]. For example, crosslinking via disulphide bonds yielded highly stable C3Ms under physiological conditions.…”
Section: Biotechnological Applications Of C3msmentioning
confidence: 99%
“…Thus, the formation of micelles is expected to weaken the 1 H-NMR signals from protons located within the micellar core due to the restricted internal molecular motion. In fact, it has been reported that the peaks from protons of molecules encapsulated in the core of micelles showed significantly decreased intensity [22][23][24]. Here, 1 H-NMR measurements were made with PIC/m prepared in a 10 mM deuterium phosphate buffer (pD = 7.0).…”
Section: Resultsmentioning
confidence: 98%
“…These PIC micelles were also employed as long-circulating enzyme carriers that maintained the enzymatic activity of catalase. pH-Responsive myoglobin-loaded PIC micelles were prepared via concurrent ion complexation and pH-cleavable amide crosslinking between the myoglobin guest and carboxy-dimethyl maleic anhydride-modified PEG- b -PLL host [ 224 ]. These micelles were stable under physiological pH with enhanced circulation time in vivo , while rapidly dissociated at pH 6.5 with the release of an intact protein payload.…”
Section: Biomedical Applications Of Pll-based Polymersmentioning
confidence: 99%